NATURAL RESTORATIVE ENVIRONMENT TERHADAP KECEMASAN PADA PASIEN CHRONIC KIDNEY DISEASES: Natural Restorative Environment on Anxiety on Patients With Chronic Kidney Diseases - Purnomo, Purnomo; Maksum, Maksum; Sujianto, Untung; Johan, Andrew; Miftakhul Nizar, Angga; Fitriani, Evi Tunjung (Jurnal Penelitian, 2023)
Chronic Kidney Disease (CKD) is a condition in which kidneys don’t function properly resulting in the accumulation of metabolic remnants. Hemodialysis therapy causes common psychological disorders, is anxiety due to changes in health status, self-acceptance, life threats, stress, and depression. Natural Restorative Environment (NRE) is an intervention that can use to reduce anxiety in patients. This study aimed to analyze the effect Natural Restorative Environment on anxiety in CKD patients on hemodialysis. The method in this research was a quasi-experiment with a pretest-posttest with a control group design. The sampling technique was carried out using cross-sectional sampling, namely 48 patients each with an intervention group and control group. Before and after the intervention, patients in the intervention group and the control group pre-test and post-test about the level of anxiety during hemodialysis therapy. Data analysis used Paired t-test, Wilcoxon-test, and Mann-Whitney U-test. The results showed a decrease in anxiety levels intervention group indicated by a p-value<0.001. Natural Restorative Environment (NRE) can be reducing anxiety in patients with CKD on hemodialysis Keywords: Anxiety; Chronic Kidneys Disease; Natural Restorative Environment